Correction: 5D total scattering computed tomography reveals the full reaction mechanism of a bismuth vanadate lithium ion battery anode. Issue 14 (22nd March 2023) - Sottmann, Jonas; Ruud, Amund; Fjellvåg, Øystein S.; Vaughan, Gavin B. M.; Di Michel, Marco; Fjellvåg, Helmer; Lebedev, Oleg I.; Vajeeston, Ponniah; Wragg, David S.
Abstract : Correction for '5D total scattering computed tomography reveals the full reaction mechanism of a bismuth vanadate lithium ion battery anode' by Jonas Sottmann et al., Phys. Chem. Chem. Phys., 2022, 24, 27075–27085, ; https://doi.org/10.1039/D2CP03892G .